The expressions that could be equivalent to x² + bx - 36 where b is negative is x² - 9x - 36 and x² - 5x - 36
check all that applies:
A. (x + 3)(x – 12)
open parenthesis
= x² - 12x + 3x - 36
= x² - 9x - 36
B. (x - 2)(x+18)
open parenthesis
= x² + 18x - 2x - 36
= x² + 16x - 36
C. (x – 13)(x – 3)
open parenthesis
= x² - 3x - 13x + 39
= x² - 16x + 39
D. (x + 4)(x + 9)
open parenthesis
= x² + 9x + 4x + 36
= x² + 13x + 36
E. (x – 9)(x+4)
open parenthesis
= x² + 4x - 9x - 36
= x² - 5x - 36
Therefore, expressions that could be equivalent to x² + bx - 36 where b is negative is x² - 9x - 36 and x² - 5x - 36
Read more:
https://brainly.com/question/1214333